The Rolling 50s (and More): Cars and Life Satisfaction Among Seniors Across Europe - Brulé, Gaël; Ravazzini, Laura; Suter, Christian (My University, 2020)
Cars represent a valuable real asset that most individuals use on a daily basis. Although cars are a form of material prosperity like income and other forms of wealth, the link between cars and subjective well-being (SWB) is barely covered in the existing literature. Furthermore, few existing contributions are scattered across specific cultural contexts. Here, we analyze the relationship between cars and the SWB of seniors in different European countries using the SHARE dataset. We construct multilevel and fixed-effect models to explore the extent of economic, infrastructural, and cultural factors and how they can explain this relationship. The results show that the value of the car is, among all wealth components (houses, bank account, bonds, stocks, mutual funds, debts and mortgages), the form of wealth most related to life satisfaction. In addition, cars matter less (a) in affluent societies, (b) where rail infrastructure is more developed, and (c) where people hold fewer materialistic values. We discuss these results in the framework of the functional and positional value of cars, i.e., respectively, the value derived from it regardless of others and the value derived from it vis-à-vis others.
Keywords: Wealth . Car . SWB . Elderly . Sustainable development . Materialistic values